REVIEW OF RELATED LITERATURE ON RESEARCH METHODS APPLIED IN TEACHING GRAMMAR USING EDUCATIONAL TECHNOLOGY - Maulina; Muhammad Ilham; Andi Hamzah Fansury (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This paper involves researching, reading, analyzing, evaluating, and summarizing related scholarly literature about research methods used in teaching grammar, utilizing educational technology as one of the research learning sources for future related research. First, the reviewed scholarly article describes how the writers conducted their research. Then, using descriptive analysis, varieties of research methods in teaching grammar utilizing educational technology are investigated. Among the investigated research methods are quasi-experimental, phenomenology, ethnography, true experimental, pre-experimental, descriptive, mixed method of an exploratory study, mixed method of explanatory study, case study, survey method, classroom action research, and collaboration research. However, due to the limited space, the paper only describes popular methods of quantitative approach, including quasi-experimental, pre-experimental, true-experimental, survey studies. Besides, the qualitative approach involves case study, descriptive study, and phenomenology. Also, one of the most popular mixed-method used is explanatory study. The description of each method is supported by examples found in international and national journal articles published worldwide. This paper is expected to be beneficial to readers and researchers in English language teaching (ELT) worldwide.